Climate change and infrastructure development drive ice-rich permafrost thaw in Point Lay (Kali), Alaska - Benjamin M Jones; Mikhail Z Kanevskiy; Billy Connor; Jana Peirce; Bill Tracey Sr; Kuoiqsik Curtis; Frank E Urban; Serina Wesen; Yuri Shur; Christopher V Maio (Environmental Research: Ecology, 2025)
Permafrost thaw and thermokarst development pose urgent challenges to Arctic communities, threatening infrastructure and essential services. This study examines the reciprocal impacts of permafrost degradation and infrastructure in Point Lay (Kali), Alaska, drawing on field data from ∼60 boreholes, measured and modeled ground temperature records, remote sensing analysis, and community interviews. Field campaigns from 2022–2024 reveal widespread thermokarst development and ground subsidence driven by the thaw of ice-rich permafrost. Borehole analysis confirms excess-ice contents averaging ∼40%, with syngenetic ice wedges extending over 12 m deep. Measured and modeled ground temperature data indicate a warming trend, with increasing mean annual ground temperatures and active layer thickness (ALT). Since 1949, modeled ALTs have generally deepened, with a marked shift toward consistently thicker ALTs in the 21st century. Remote sensing shows ice wedge thermokarst expanded from <5% in 1949 to >60% in developed areas by 2019, with thaw rates increasing tenfold between 1974 and 2019. In contrast, adjacent, undisturbed tundra exhibited more consistent thermokarst expansion (∼0.2% yr ^−1 ), underscoring the amplifying role of infrastructure, surface disturbance, and climate change. Community interviews reveal the lived consequences of permafrost degradation, including structural damage to homes, failing utilities, and growing dependence on alternative water and wastewater strategies. Engineering recommendations include deeper pile foundations, targeted ice wedge stabilization, aboveground utilities, enhanced snow management strategies, and improved drainage to mitigate ongoing infrastructure issues. As climate change accelerates permafrost thaw across the Arctic, this study highlights the need for integrated, community-driven adaptation strategies that blend geocryological research, engineering solutions, and local and Indigenous knowledge.